Skrining Potensi Essential Oil Pogostemon Cablin Bent Secara In Silico dalam Penghambatannya terhadap ACE II dan TMPRSS2 sebagai Anti Covid-19 - Yoni Rina Bintari; Dini Sri Damayanti (Publikasi oleh Fakultas Kedokteran Universitas Islam Malang, 2022)
Abstract. COVID-19 is a disease caused by a coronavirus class virusthatis known to enter humans by means of the Spike protein (S) binding toACEII (Angiotensin Coverting Enzyme) and then being activated byTMPRSS2 (Transmembrane Protease, Serine). COVID-19 has become apandemic, so it requires agents that act as anti-Covid-19. Pogostemoscablin bent is an herb that contains EO (Essential oil) and is widelygrown in Indonesia. EO is known to have potential as an antivirus. Thisstudy aims to predict the EO potential of P. Cablin as anticovid-19through a molecular docking approach by measuring its inhibition ofACE II (Q9BYF1) and TMPRSS2 (7MEQ). The inhibitory potential wascalculated from the binding affinity using Pyrex Autodock Vina software. The docking results are then visualized using Biovia DiscoveryStudio and PyMOL. Prediction of physicochemical and pharmacokineticprofiles through pKCsm web. The docking results showed that pachuolialcohol inhibited ACEII and TMPRSS2 with gibs energy of -7.7 kcal/mol,respectively, through the interaction of hydrogen His 383 and Asp 415and -5.8 kcal/mol through the interaction of hydrogen Leu 248. However, the mechanism of inhibition of pachuoli alcohol was different fromthat of chloroquine (Clq) and napamosphate. Clq inhibits ACE II throughthe amino acid residue Thr 282 with a gibs energy of -6.7 kcal/mol.Nafamosfat inhibits TMPRSS2 through amino acid residues Ser 333, Pro335, Tyr 337 with a gibs energy of -8.3 kcal/mol. Predictive results ofphytochemical screening and pharmacokinetic profiles indicate thatpachuoli alcohol is a potential drug candidate.